1997
DOI: 10.7863/jum.1997.16.11.743
|View full text |Cite
|
Sign up to set email alerts
|

Isolated splenic metastases.

Abstract: We analyzed the primary tumors, sonographic findings, clinical manifestations, and prognosis in five cases of isolated splenic metastases to determine in what situations these rare metastases should be suspected. The metastases were detected by ultrasonography in all five patients, and the primary tumors were colonic cancer in four patients and renal cancer in one patient. Splenectomy was performed and the postoperative course was uneventful in all patients. We conclude that preoperative and follow-up examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 2 publications
0
24
0
4
Order By: Relevance
“…Twenty-one cases were separately reported and five cases were described in two reports of patients with splenic metastases (one case in Lee et al [20] and four cases in Ishida et al [17]). Only four cases were diagnosed with synchronous splenic metastasis; the remaining 22 cases were classified as metachronous, with a median diseasefree interval of 40 months (range 3-144 months).…”
Section: Methods and Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Twenty-one cases were separately reported and five cases were described in two reports of patients with splenic metastases (one case in Lee et al [20] and four cases in Ishida et al [17]). Only four cases were diagnosed with synchronous splenic metastasis; the remaining 22 cases were classified as metachronous, with a median diseasefree interval of 40 months (range 3-144 months).…”
Section: Methods and Resultsmentioning
confidence: 96%
“…Only 26 cases of isolated solitary splenic metastasis from colorectal carcinoma have been reported in the English-language literature (Tables 1, 2) [4,5,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Twenty-one cases were separately reported and five cases were described in two reports of patients with splenic metastases (one case in Lee et al [20] and four cases in Ishida et al [17]).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Imada et al 29 in 1991, these lesions usually appear as low-density masses at the computed tomography, while echography shows images of hypoechoic or hyperechoic patterns 6,29 . On the other hand, in 1997, Ishida et al 30 published a study in which they identified by echography the presence of four cases of splenic metastasis of primary colon cancer, then suggesting the importance of special attention to the spleen of a patient diagnosed with CRC, either in staging or follow-up 6,30 . In the follow-up period, increasing CEA values may suggest tumor recurrence, requiring a complementary investigation to identify the possible metachronous metastatic focus.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent autopsy series found an incidence of 3% [5]. The advent of imaging techniques using ultrasound and cross-sectional imaging have demonstrated metastatic disease in the spleen in 0.15% of patients in a Japanese study of ultrasound imaging [6] and non-haematological malignancy was found in 1.3% of sequential splenectomy specimens at two centers in the USA [7]. A Chinese study reported 92 cases of splenic metastases in non-haematological malignant disease-an autopsy incidence of 0.6% and 1.1% of splenectomies were undertaken for metastatic disease during the study period [8].…”
Section: Introductionmentioning
confidence: 97%